Social inequality, criminal justice, and race in Tennessee : 1960-2014 - Fosten, Gerald K. (Lexington Books, 2018)
This book examines the national criminal justice system's and the state of Tennessee criminal justice system's policies in terms of how they balance the citizens' need for prisons with the private sector's desire for profits and the policies' effects on the incarceration rate of African American males in the state of Tennessee.